Implementasi Sistem Absensi Peserta Magang Berbasis Web Menggunakan Metode Waterfall - Arinda Aulia; Falah Affandi; Yusuf Ramadhan Nasution (Jurnal ilmiah Sistem Informasi dan Ilmu Komputer, 2025)
The internship attendance process for students in government institutions is still carried out manually, which often leads to irregularities and inefficiencies in recording attendance. To address this issue, this study designs a web-based attendance system for internship participants at the Regional House of Representatives (DPRD) of North Sumatra using the Waterfall method. This method was chosen because it provides a structured sequence of stages, starting from requirements analysis, system design, implementation, testing, and maintenance. Through this approach, system requirements can be clearly analyzed from the beginning, resulting in a design that aligns with the intended goals. The developed system features user login, attendance input for internship participants, attendance data recap, and report generation. The results show that this web-based attendance system improves the efficiency of attendance recording, minimizes errors, and creates a more organized internship environment. Therefore, the implementation of a web-based attendance system using the Waterfall method can serve as an effective and structured solution to support the management of internship attendance data.